Childhood football play and practice in relation to self-regulation and national team selection; a study of Norwegian elite youth players - Erikstad, M. E.; Høigaard, R.; Johansen, B. T.; Kandala, N.-B.; Haugen, T. (Journal of Sports Sciences, 2019)
Childhood sport participation is argued to be important to understand differences in self-regulation and performance level in adolescence. This study sought to investigate if football-specific activities in childhood (6-12 years of age) is related to self-regulatory skills and national under 14- and 15-team selection in Norwegian elite youth football. Data of practice histories and self-regulatory skills of 515 youth football players selected at Norwegian regional level were collected and further analysed using multilevel analyses. The results revealed that high self-regulated players were more likely to be selected for national initiatives, and increased their involvement in peer-led football practice and adult-led football practice during childhood, compared to players with lower levels of self-regulation. While national level players reported higher levels of peer-led football play in childhood, the interaction effect suggest that the regional level players increased their involvement in peer-led play during childhood compared to national level players. In conclusion, the findings indicate that childhood sport participation may contribute to later differences in self-regulation, and highlights the importance of childhood engagement in football-specific play and practice in the development of Norwegian youth football players.